Polypropylene suture as a seton in recurrent fistula-in-ano in lower socioeconomic class-a good option - Patel, Kiran (International Surgery Journal, 2021)
Background: Recurrent anal fistulas after previous fistula surgery are a unique problem that typically necessitates more anal surgical experience to address the cause of recurrence. The present study was planned with the objective to determine the outcomes of the polypropylene suture as a seton placement for the treatment of recurrent anal fistula. Methods: Patients between the ages of 20-80 years with recurrent fistula-in-ano with single external opening and with history of previous surgery. Patients with preoperative incontinence, patients with difficult follow-up and who were not ready to participate in the study, patients with fistulas caused by inflammatory bowel disease, malignancy, tuberculosis, or trauma, patients with a horseshoe or multiple fistulas, patients with recurrent fistula-in-ano with multiple external opening, or recurrent fistula-in-ano with diseases like Crohn’s disease, tuberculosis, actinomycosis, malignancy, or high level fistula-in-ano without internal opening, and patients with synchronous anorectal problems such as haemorrhoids were excluded. Results: Post-operative pain was observed in all patients while discharge, bleeding and inflammation were observed in 27, 10 and 8 patients, respectively on day 0. Majority of post-operative symptoms were resolves in almost all patients except, pain and discharge were observed in 2 and 1 patients, respectively on day 7. At 6 months follow-up, incontinence of flatus was found out in 2 patients while no patient had incontinence of faeces. Conclusions: Polypropylene suture as a seton in recurrent fistula-in-ano, in previously operated patient is safe and most acceptable treatment. Ksharsutra is not easily available but polypropylene suture is easily available.